Simultaneous determination of glucose, fructose, sucrose and sorbitol in the leaf and fruit peel of different apple cultivars by the HPLC–RI optimized method. (15th May 2016) - Filip, Miuţa; Vlassa, Mihaela; Coman, Virginia; Halmagyi, Adela
Highlights: A HPLC–RI method for the simultaneous determination of sugars in leaf and apple peel. Box–Behnken design of RSM methodology was applied to the method optimization. HPLC–RI method was validated for linearity, LOD, LOQ, precision and recovery. A comparative HPLC–RI evaluation of sugars from plant material categories was done. Abstract: A high performance liquid chromatography method with refractive index detection (HPLC–RI), for simultaneous determination of glucose, fructose, sucrose and sorbitol in leaf and/or apple peel samples from nine apple ( Malus domestica Borkh.) cultivars and rootstocks, originating from a germplasm collection, has been developed and validated. Box–Behnken design of response surface methodology was applied for the method optimization. The Carbosep Coregel 87H3 column was used under the optimum conditions predicted: mobile phase of H2 SO4 0.005 mol L −1 solution, flow rate of 0.3 mL min −1 and column temperature of 35 °C. The method was validated for linearity ( R 2 > 0.99), limits of detection (2.67–4.83 μg mL −1 ) and quantification (8.9–16.1 μg mL −1 ), precision (%RSD < 5.05) and recovery (93.94–103.06%) and satisfactory results obtained. The sugars content varied across micropropagated plants in vitro, plants regenerated after cryostorage, growing trees in vivo, and fruit peel.